2012
DOI: 10.1007/s10059-012-0182-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Promoter Methylation and Histone Modification Contribute to the Brain Specific Expression of the Mouse Mbu-1 Gene

Abstract: Mbu-1 (Csrnp-3) is a mouse gene that was identified in our previous study as showing highly restricted expression to the central nervous system. In this study, to elucidate the regulatory mechanism for tissue specificity of the gene, epigenetic approaches that identify the profiles of CpG methylation, as well as histone modifications at the promoter region were conducted. Methylation-specific PCR revealed that the CpG sites in brain tissues from embryo to adult stages showed virtually no methylation (0.052-0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Histones are known to undergo specific modification such as methylation and acetylation: while methylation and demethylation of histone are coordinated by histone methyltransferases (HMTs) and demethylase (HDMs), acetylation of histone is modulated by acetyltransferases (HAT) and deacetylases (HDAC) ( Bhaumik et al, 2007 ; Helin and Dhanak, 2013 ). Due to their significance in regulating genetic program during development and diseases, recent efforts were directed to identify specific factors that mediate this process ( Arrowsmith et al, 2012 ; Cayuso Mas et al, 2011 ; Kim et al, 2012a ; 2012b ). In case of methylation, histone H3 lysine 4 residue (H3K4) is sequentially modified through mono-, di-, and tri-methylation status, each of which step is mediated by specific enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Histones are known to undergo specific modification such as methylation and acetylation: while methylation and demethylation of histone are coordinated by histone methyltransferases (HMTs) and demethylase (HDMs), acetylation of histone is modulated by acetyltransferases (HAT) and deacetylases (HDAC) ( Bhaumik et al, 2007 ; Helin and Dhanak, 2013 ). Due to their significance in regulating genetic program during development and diseases, recent efforts were directed to identify specific factors that mediate this process ( Arrowsmith et al, 2012 ; Cayuso Mas et al, 2011 ; Kim et al, 2012a ; 2012b ). In case of methylation, histone H3 lysine 4 residue (H3K4) is sequentially modified through mono-, di-, and tri-methylation status, each of which step is mediated by specific enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we can highlight several genes which encode for proteins with specific neuronal function, found to be upregulated in males. i.e., the MSRA gene in SN control samples (TRAM CTR, Table 2 ), whose product has a key role in oxidative stress response and a high expression in the brain, including the SN, with a higher immuno-reactivity in neurons than in glial cells [ 56 , 57 ]; the SCN3A and SCN2A genes, that encode for glycoprotein members of a family of voltage-gated sodium channels involved in the generation and propagation of action potentials in neurons and muscle cells [ 58 , 59 ]; the CSRNP3 gene, encoding for a transcriptional activator, whose mouse ortholog Mbu-1 shows a high expression in the central nervous system, in particular in the brain and spinal cord in the course of embryonic development but also in adults [ 60 ]; the NSUN2 gene, whose product is a methyltransferase involved in the stabilization of the anticodon-codon pairing and the correct translation of the mRNA, and whose loss-of-function is associated with increased cellular stress and neurodevelopmental disorders [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a 4.1 kb CSRNP2 transcript has been detected in numerous mammalian organs, especially in the brain, ovary, and thymus. Finally, CSRNP3 (also known as Mbu-1 ) is a brain-specific gene ( 10 ); it is expressed in the brain and spinal cords of embryonic to adult mice only ( 11 ). These findings suggested that the CSRNP gene family might have great value in different cancers.…”
Section: Introductionmentioning
confidence: 99%